2020
DOI: 10.21037/jtd-20-905
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide quality assessment of treatment for chronic obstructive pulmonary disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) requires careful ambulatory care. If treatment is effective, exacerbation and hospitalization can be preventable. Appropriate management is important; the disease prevalence is high, as is the demand on healthcare resources. Here, we have reported the results of nationwide quality assessment performed with the aims of improving patient management, reducing progression to severe status, and minimizing medical care expenses. Methods: The Health Insurance R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These findings are similar to rates of use of spirometry to confirm diagnosis reported in other countries such as Denmark, Sweden, and the United States, 22 , 23 , 24 but higher than in South Korea. 25 There was also evidence that rather than improving over time, there has been a decline in the proportion of patients who have had spirometry at diagnosis in recent years, despite guidance from the national health outcomes strategy, NICE, and international guidelines/strategy documents. There is, therefore, a clear opportunity to improve COPD management by increasing the use of spirometry to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to rates of use of spirometry to confirm diagnosis reported in other countries such as Denmark, Sweden, and the United States, 22 , 23 , 24 but higher than in South Korea. 25 There was also evidence that rather than improving over time, there has been a decline in the proportion of patients who have had spirometry at diagnosis in recent years, despite guidance from the national health outcomes strategy, NICE, and international guidelines/strategy documents. There is, therefore, a clear opportunity to improve COPD management by increasing the use of spirometry to confirm the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to clinically significant improvements in symptoms, exercise capacity, and health-related quality of life, and results in fewer and shorter hospital stays and readmission, 31 and is recommended for all patients with exercise limitation due to breathlessness. 19 , 25 Referral rates are included in the NICE QS 20 and feature in QOF; however, only approximately one-third of newly diagnosed patients and half of already diagnosed patients had been offered or received a PR referral. To some extent this may reflect the poor availability and capacity of PR programmes 32 but improving access to PR and referring appropriate patients offers another important opportunity to improve patients’ wellbeing and reduce hospitalisation rates.…”
Section: Discussionmentioning
confidence: 99%
“…16 The same study showed that in 2019, the most recent year analysed, over 40% of newly diagnosed patients had not had spirometry recorded in the previous year. Studies in other countries such as Wales, Denmark, Sweden, Korea and the USA, [17][18][19][20][21] have also shown poor levels of confirmation of the diagnosis with spirometry. Disappointingly, the English data also showed that, despite dissemination of national and international guidance, there had been a decline in the proportion of patients who had had spirometry at diagnosis in recent years.…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, Kim et al reported the first, second and third results from May 2014 to April 2017. During the 3 consecutive years of nationwide quality assessment, the PFT test implementation and inhaled bronchodilator prescription rates improved (29). The quality assessment results are published annually by the HIRA and shared with healthcare institutions.…”
Section: Treatment Statusmentioning
confidence: 99%